Silencing lncRNA TUG1 Alleviates LPS-Induced Mouse Hepatocyte Inflammation by Targeting miR-140/TNF - Liu, Qing-Min; Liu, Li-Li; Li, Xi-Dong; Tian, Ping; Xu, Hao; Li, Zeng-Lian; Wang, Li-Kun (Frontiers in Cell and Developmental Biology, 2021)
Hepatitis is a major public health problem, which increases the risk of liver cirrhosis and liver cancer. Numerous studies have revealed that long non-coding RNAs (lncRNAs) exert essential function in the inflammatory response of multiple organs. Herein, we aimed to explore the effect of lncRNA TUG1 in LPS-induced hepatocyte inflammation response, and further illuminate the underlying mechanisms. Mice were intraperitoneally injected with LPS, and the liver inflammation was evaluated. Microarray showed lncRNA TUG1 was up-regulated in LPS-induced hepatocyte inflammation. Followed qRT-PCR and immunofluorescence assay indicated a significant increase of TUG1 in mice with LPS injection. Functional analysis showed that si-TUG1 inhibited LPS-induced inflammation response in mice liver, and inhibited apoptosis level, and protected liver function. Then, we knockdown TUG1 in normal human hepatocyte AML12. Consistent with in vivo results, si-TUG1 removed the injury of LPS on AML12 cells. Furthermore, TUG1 acted as a sponge of miR-140, and miR-140 directly targeted TNFα (TNF). MiR-140 or si-TNF remitted the beneficial effects of TUG1 on LPS-induced hepatocyte inflammation response both in vitro and in vivo. Our data revealed that deletion of TUG1 protected against LPS-induced hepatocyte inflammation via regulating miR-140/TNF, which might provide new insight for hepatitis treatment.